The US-India Civil Nuclear Pact: Policy, Process, And Great Power Politics - Sharma, Madhubala (International Journal of Psychosocial Rehabilitation, 2013)
This article examines the process through which India and the United States made their bilateral civilian nuclear energy cooperation pact a reality. Using the levels of analysis approach, this article examines the factors that were instrumental in shaping up the nuclear agreement as well as the negotiating process as it evolved in the United States and India with a special focus on how political leaderships in the two states managed domestic opposition to thepact. Subsequently, this article locates the US-India nuclear agreement in the context of the broader theoretical debate in international relations over the role of international institutions in global politics and argues that the successful conclusion of the agreement highlights the importance of strategic considerations in driving the nonproliferation priorities of great powers